Characterisation and development of rubberised bitumen and asphalt mixture based on performance-related requirements - Subhy, Ayad Tareq (2017)
Incorporating recycled tyre rubber into flexible pavement applications by means of Recycled Tyre Rubber-Modified Bitumen RTR-MBs would solve a serious waste problem, save energy and materials, and enhance pavement life and performance. On the other hand, the excessive high-temperature viscosity of rubberised binders imposes handling difficulties during the mixing and compaction process. Therefore, producing rubberised binders with acceptable high-temperature viscosity, and equally having desirable mechanical properties that are truly reflected in asphalt mixtures, was the main aim of this study. Three different types of recycled tyre rubber, with two different base bitumens, were selected to produce different combinations of rubberised binders. The three different sources of recycled tyre rubber are; (1) normal ambiently produced tyre rubber (2) cryogenically produced tyre rubber that was pre-treated with Warm Mix Additive (Sasobit®) in order to reduce the high-temperature viscosity of rubberised binders and (3) normal ambiently produced recycled tyre rubber containing 20% devulcanised rubber. The two base bitumens were selected with large differences in their physical and rheological properties in order to identify the effect of the base bitumen on the interaction mechanism and the final rubberised bitumen properties; a hard base bitumen with a penetration of 40 dmm and a soft bitumen with a penetration of 200 dmm were, therefore, chosen. The laboratory experimental design has been divided into three main parts in order to accomplish the main objectives of the study; Part 1: Optimise the blending variables (temperature and time) based on the rheological characteristics of binders. This was carried out through low shear mixing by using the Brookfield Viscometer with a modified Dual Helical Impeller (DHI). The blending variables (temperature and time) were investigated based on their influence on measurements of the linear and nonlinear viscoelastic properties. The rheological measurements including dynamic mechanics analysis (DMA) and Multiple Stress Creep Recovery (MSCR) tests were conducted using the Dynamic Shear Rheometer (DSR). Part 2: Manufacture the rubberised bitumens by using the Silverson L4RT High Shear Mixer based on the optimised blending variables that were identified from Part 1. The produced rubberised bitumens in addition to their base bitumens were characterised for their fatigue and rutting properties. Different test methods were used to evaluate the fatigue and rutting resistance of binders. The fatigue testing involved the SHRP parameter, Time Sweep tests and the essential work of fracture using the double-edged notched tension (DENT) test. The dissipated energy approach was used to characterise the fatigue properties of binders. The effect of artificial ageing (short and long term ageing) was also investigated. The rutting testing involved the SHRP parameter, Shenoy Parameter, Zero Shear Viscosity, and non-recoverable compliance Jnr from the MSCR test. Part 3: A typical stone mastic gradation (10mm) suitable for surface courses was selected from the British specification BS EN 13108-5/ PD 6691:2007 for designing rubberised bitumen mixtures (using the different rubberised bitumens from Part 2) in addition to the control mixture (without rubber). The fatigue and rutting properties of different mixtures were evaluated. The fatigue testing was carried out using the Indirect Tensile Fatigue Test in the Nottingham Asphalt Tester (NAT machine) equipment and SuperPave Indirect Tensile Test IDT using the INSTRON. The rutting was evaluated using the Repeated Load Axial Test (RLAT) in the NAT machine. Also, the mixture testing included evaluating the stiffness of mixtures and moisture susceptibility using the Indirect Tensile Stiffness Test (ITSM). The results of this work have indicated that pre-treatment of the recycled rubber can significantly reduce the high-temperature viscosity; however, the fracture properties of binders are compromised, i.e. it makes the bituminous binders fragile and hence more susceptible to cracking. In general, the addition of rubber can produce bituminous materials with enhanced rutting and fatigue characteristics. This is especially evident for rubberised bitumen manufactured using very soft base bitumen (200 dmm penetration). The results of the RLAT have revealed that mixtures made using this binder were even more rutting resistant than mixtures made using the hard base bitumen H (40 dmm penetration). Such results suggest that rubberised bitumens produced with a very soft base bitumen can be a very effective option for pavements that are prone to both low temperature cracking and permanent deformation. All test methods and parameters, for binders and mixtures, have proven that the addition of rubber can improve the fatigue and rutting properties of materials.